Floristic composition of the coastal district Satkhira, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
This study presents elementary taxonomic data on the composition of vascular flora in the disaster prone coastal district Satkhira of Bangladesh. The results of this study show that this district houses 664 species under 468 genera and 133 families of vascular plants. The Pteridophytes and Gymnosperms are represented by 21 and five species, whereas, the Magnoliopsida (dicotyledons) and Liliopsida (monocotyledons) of Angiosperms by 494 and 144 species, respectively. About 59.64% of these species are herbs, 15.96% shrubs, 21.69% trees, 2.26% palms and 0.45% bamboos. Total 73.04% of the species are wild, 19.88% planted and 7.08% cultivated. In this area, Fabaceae with 31 species is the largest family, followed by Asteraceae with 27 species, Apocynaceae with 26 species and Malvaceae with 25 and Acanthaceae with 22 species. Ficus with seven species is recorded as the largest genus, which is followed by Solanum, Hygrophila, Euphorbia, Senna, Phyllanthus, Ipomoea, Hibiscus and Alternanthera. Most of the species are found in fallow lands, roadsides, woodlands, homesteads and scrub jungles and useful as medicine, ornamental, fibre, fruit, livestock feed, soil binder and timber. The floristic composition of this district is still rich, though most of its habitats and ecosystems are vulnerable to natural disasters. Effective conservation plan and measures should be adopted for the precious flora of this coastal district.Bangladesh J. Plant Taxon. 28(1): 97-124, 2021 (June)